The Coevolution of Massive Quiescent Galaxies and Their Dark Matter Halos over the Last 6 Billion Years - Zahid, H. Jabran; al., et (The Astrophysical Journal, 2019)
We investigate the growth of massive quiescent galaxies at z < 0.6 based on the Sloan Digital Sky Survey and the Smithsonian Hectospec Lensing Survey, two magnitude-limited spectroscopic surveys of high data quality and completeness. Our three-parameter model links quiescent galaxies across cosmic time by self-consistently evolving stellar mass, stellar population age-sensitive Dn4000 index, half-light radius, and stellar velocity dispersion. Stellar velocity dispersion is a robust proxy of dark matter halo mass; we use it to connect galaxies and dark matter halos and thus empirically constrain their coevolution. The typical rate of stellar mass growth is , and dark matter growth rates from our empirical model are remarkably consistent with N-body simulations. Massive quiescent galaxies grow by minor mergers with dark matter halos of mass and evolve parallel to the stellar mass–halo mass (SMHM) relation based on N-body simulations. Thus, the SMHM relation of massive galaxies apparently results primarily from dry minor merging.